2021
DOI: 10.1051/0004-6361/202039620
|View full text |Cite
|
Sign up to set email alerts
|

Detection of new O-type stars in the obscured stellar cluster Tr 16-SE in the Carina Nebula with KMOS

Abstract: Context. The Carina Nebula harbors a large population of high-mass stars, including at least 75 O-type and Wolf-Rayet (WR) stars, but the current census is not complete since further high-mass stars may be hidden in or behind the dense dark clouds that pervade the association. Aims. With the aim of identifying optically obscured O- and early B-type stars in the Carina Nebula, we performed the first infrared spectroscopic study of stars in the optically obscured stellar cluster Tr 16-SE, located behind a dark d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Not being a true cluster, Villafranca O-025 does not show a central concentration and the limits traditionally assigned to Trumpler 16 are established actually by the V-shaped dust lane immediately to its south, which is placed in the foreground with respect to the Carina nebula (top left plot in Fig. 7 of Maíz Apellániz & Barbá 2018, see also Preibisch et al 2021). Nevertheless, the stellar population of Villafranca O-025 is relatively easy to identify thanks to its richness and to its relatively low extinction in comparison with the background stars.…”
Section: Villafranca O-025 = Trumpler 16 Ementioning
confidence: 94%
See 1 more Smart Citation
“…Not being a true cluster, Villafranca O-025 does not show a central concentration and the limits traditionally assigned to Trumpler 16 are established actually by the V-shaped dust lane immediately to its south, which is placed in the foreground with respect to the Carina nebula (top left plot in Fig. 7 of Maíz Apellániz & Barbá 2018, see also Preibisch et al 2021). Nevertheless, the stellar population of Villafranca O-025 is relatively easy to identify thanks to its richness and to its relatively low extinction in comparison with the background stars.…”
Section: Villafranca O-025 = Trumpler 16 Ementioning
confidence: 94%
“…The census should be complete in the region barring the unknown classification of η Car B and (unlikely) objects hidden by large extinction and source confusion(Smith 2006a;Preibisch et al 2021). …”
mentioning
confidence: 99%
“…IMPS with spectral types G through early K are the progenitors of zero-age main-sequence (ZAMS) late-B through A-type stars. Fully radiative AB stars possess neither magnetic dynamos nor sufficiently strong winds to power the shock-driven X-rays commonly observed from massive, O-and early-B-type stars (Gagné et al 2011;Nazé et al 2011;Preibisch et al 2021). This implies that any intrinsic X-ray emission from convective IMPS should disappear over timescales shorter than the <10 Myr ZAMS arrival times of >2M e stars (Siess et al 2000;Haemmerlé et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This sample was complemented by 15 additional OB stars in the Carina Nebula listed in Shull et al (2021). We also added 8 OB stars which were recently identified in the cluster Tr16-SE (Preibisch et al 2021), the 5 OB stars known in NGC 3324 (see Preibisch et al 2014a), and 99 B stars from NGC 3293 (Evans et al 2005). This results in a sample of 241 OB stars in the CNC.…”
Section: Construction Of the Ob Star Samplementioning
confidence: 99%
“…A study of the Gaia EDR3 data for 69 massive stars in the central Carina Nebula by Shull et al (2021) found a common distance of (2.35 ± 0.08) kpc for these stars and no significant differences in the distances of the central Carina Nebula clusters Tr 14, 15, and 16. As pointed out by the authors, the controversy over the 1 A good example for the strong spatial variations of cloud extinction in the Carina Nebula is the highly obscured cluster Tr 16-SE (see Preibisch et al 2021): the stars in Tr 16-SE suffer extinctions of A V > ∼ 5 − 10 mag, making them very faint or invisible in optical images, although they are located just a few arcminutes south of the (much less obscured and therefore optically much brighter) stars of the cluster Tr 16.…”
Section: Introductionmentioning
confidence: 99%